TRACE ELEMENTS AND SR AND C ISOTOPIC SIGNATURES IN LATE NEOPROTEROZOIC AND EARLIEST CAMBRIAN SEDIMENTARY ORGANIC MATTER FROM SILICICLASTIC SUCCESSIONS IN THE EAST EUROPEAN PLATFORM - Felitsyn S.B.; Vidal G.; Moczyudłowska M. (My University, 1998)
Sedimentary organic matter deriving from tubes of sabelliditids, vendotaenids, sapropelic films and kerogens was extracted by acid processing from Upper Vendian siliciclastic successions in the East European Platform. Elemental composition obtained by instrumental neutron activation analysis (INAA) displays the increasing cobalt (Co) concentration from 1 ppm at the bottom of Upper Vendian succession to about 800 ppm in the uppermost part near the Precambrian 13C and Co imply the secondary isotopic signatures of Sr and C in sedimentary organic matter deriving from a restricted epicontinental marine basin.
Keywords: Neoproterozoic; Cambrian; Докембрий::Протерозой::Неопротерозойская; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic; Палеозой::Кембрийская